2019
DOI: 10.1002/pon.5023
|View full text |Cite
|
Sign up to set email alerts
|

The role of trait emotional intelligence in quality of life, anxiety and depression symptoms after surgery for esophageal or gastric cancer: A French national database FREGAT

Abstract: Objective The main objective was to test the indirect effects of emotional competence (EC) after diagnosis (T1) on the health‐related quality of life (HRQoL) after surgery (T2) of esogastric cancer patients via fewer anxiety and depression symptoms (T2). Methods Data were collected from 30 French centers via the clinicobiological database French EsoGastric Tumors (FREGAT). Two hundred and twenty‐eight participants completed a self‐reported questionnaire at T1 and T2, assessing their EC (Profile of Emotional Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 38 publications
(121 reference statements)
11
34
0
Order By: Relevance
“…Pearson's correlations were used to examine the construct validity of the Short-PEC with the other scales. EC, especially intrapersonal EC, should be correlated negatively with the anxiety and depression symptoms and the impaired HRQoL of patients, as previously found with the Full-PEC [7,17].…”
Section: Plos Onesupporting
confidence: 73%
See 3 more Smart Citations
“…Pearson's correlations were used to examine the construct validity of the Short-PEC with the other scales. EC, especially intrapersonal EC, should be correlated negatively with the anxiety and depression symptoms and the impaired HRQoL of patients, as previously found with the Full-PEC [7,17].…”
Section: Plos Onesupporting
confidence: 73%
“…It is important to evaluate and reinforce their EC in psychosocial interventions to facilitate the cognitive and emotional processes required for a better adjustment to the disease and its treatments (e.g. emotional distress, quality of life, supportive care needs) [7,8,17].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[1218] Previous studies found that patients with GC who received EGCR often have psychological disorders. [19–32] Although numerous studies reported that advanced care (AC) can help relieve psychological disorders in GC patients who received EGCR. [20–32] However, no evidence on levels of evidence-based medicine is provided.…”
Section: Introductionmentioning
confidence: 99%